Genetic diversity in the growth of white jabon (Neolamarckia cadamba) provenance-progeny test: Comparing study in the nursery and field - DEDE J SUDRAJAT; YULIANTI YULIANTI; EVAYUSVITA RUSTAM; ICHSAN SUWANDHI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sudrajat DJ, Yulianti, Danu, Rustam E, Suwandhi I. 2019. Genetic diversity in the growth of white jabon (Neolamarckia cadamba) provenance-progeny test: Comparing study in the nursery and field. Biodiversitas 20: 1325-1332. Results of the provenance-progeny test in seedling and field test of white jabon (Neolamarckia cadamba) at Parung Panjang, Bogor District, West Java Province, Indonesia are reported and discussed. Twelve provenances representing 105 families were tested in nursery and field using randomized complete block design. Seedling height, root collar diameter, sturdiness quotient, shoot dry weight, root dry weight and shoot-root ratio was measured at four months, while as the growth assessment was carried out on survival, height and stem diameter at the age of 2 and 4 years. The result showed that genetic variation was found to be higher among families within provenances than the variation among provenances for all parameters indicating the family effect had the highest contribution on the growth and survival. Based on family and provenance mean, most of the seedling parameters were significantly correlated with the others, but most of seedling parameters were not significantly correlated with plant growth at 2 and 4 years. The longitudinal cline was significantly correlated with shoot dry weight, root dry weight, and shoot-root ratio indicated that the white jabon seeding parameters in natural populations may have greater in humid (higher precipitation) than in drier locations. This was likely to suggest that the family or provenance selections based on seedling growth in the nursery may not be very effective because heritability of most growth variables is likely to be low.